PENGARUH DISIPLIN KERJA DAN ETOS KERJA TERHADAP KOMPENSASI DIREKTORAT JENDERAL PEMBINAAN HUBUNGAN INDUSTRIAL JAMINAN SOSIAL TENAGA KERJA - Mahendra, Arisfa; Susanto, Andi Heru (Lembaga Pengembangan Kinerja Dosen, 2023)
Work discipline and work ethic that have been applied, good and in accordance with expectations will make an employee will be satisfied with his work. Applying high work discipline can improve the performance and achievement of the goals of the employee agency to the maximum. Therefore, this study aims to determine the influence of work discipline and work ethic on employee compensation. This research is a quantitative study in which the data analysis techniques used are, multiple linear regression tests, simultaneous tests (f), and partial tests (t). The number of samples in this study was 80 respondents with 25 statements on the questionnaire. This study used SPSS analysis tool version 25. The results of this study show that there is a positive and significant influence between work discipline and work ethic both simultaneously and partially on employee compensation of the Directorate General of Industrial Relations Development and Labor Social Security.